Factors Related to Intention to Undergo Female Sterilization Among Married Women in Rural Kathmandu, Nepal - Dhungana, Adhish; Nanthamongkolchai, Sutham; Pitikultang, Supachai (Nepal Journal of Epidemiology, 2016)
Background: Sterilization is most widely used fertility regulation method in Nepal. However, prevalence of uptake of female sterilization in central hilly region is less than the national average. The objective of the study was to explore the number and factors related to intention of married women to undergo female sterilization in rural Kathmandu which lies within central hilly region. Materials and Methods: This is a community based cross-sectional survey research conducted in rural area of Kathmandu valley. Two hundred and forty currently married women with at least one child of any age were interviewed using a structured pre-tested questionnaire. Results: More than four-fifth of the respondents intended to undergo sterilization. Almost two-third of them wanted to limit their family size by taking this option. More than one-third of women not-intending to undergo sterilization feared weakness after sterilization. Age of the respondents, duration of marriage, and number of living children were significantly associated with intention to undergo sterilization. 15-24 years age group were six times more likely to have the intention for sterilization (OR 6.79, CI 2.28-20.19) compared to age 35 years and above group. Mothers with less than 3 living children are about three times more likely to have the intention to undergo sterilization (OR 2.87, CI 1.3-6.33) compared to women with more than 2 living children. Women married for 6 to 10 years were three times more likely to have the intention (OR 3.0, CI 1.09-8.27). However, gender of the living children was not associated with intention to undergo sterilization. Conclusion: There were significant numbers of women intending to undergo sterilization. Age of the mother, number of living children and the duration of marriage were found to be significantly influencing the intention to undergo sterilization. However, as intention refers to future plan, the respondents’ intention may change over time. The national family planning program also needs to identify the key factors in accepting the sterilization and target these women to increase utilization.